2011
DOI: 10.1007/s00203-010-0669-2
|View full text |Cite
|
Sign up to set email alerts
|

Two promoters and two translation start sites control the expression of the Shigella flexneri outer membrane protease IcsP

Abstract: The Shigella flexneri outer membrane protease IcsP proteolytically cleaves the actin-based motility protein IcsA from the bacterial surface. The icsP gene is monocistronic and lies downstream of an unusually large intergenic region on the Shigella virulence plasmid. In silico analysis of this region predicts a second transcription start site 84 bp upstream of the first. Primer extension analyses and beta-galactosidase assays demonstrate that both transcription start sites are used. Both promoters are regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Promoter activity of this gene was measured using a plasmid-borne P icsP-lacZ reporter in both E. coli and Shigella backgrounds [50,52]. While 5′ truncation analyses of the icsP promoter reveal that the DNA sequences located between 800 and 350 bp upstream of the primary icsP TSS are required for H-NS-mediated repression [60], the VirB binding site required for transcriptional anti-silencing of this promoter lies over 1 kb upstream of the primary icsP TSS [52,61]. To date, it remains unclear how silencing and anti-silencing of the icsP promoter occurs from such remote sites.…”
Section: H-ns and Its Role In The Regulatory Cascade Controlling Tmentioning
confidence: 99%
“…Promoter activity of this gene was measured using a plasmid-borne P icsP-lacZ reporter in both E. coli and Shigella backgrounds [50,52]. While 5′ truncation analyses of the icsP promoter reveal that the DNA sequences located between 800 and 350 bp upstream of the primary icsP TSS are required for H-NS-mediated repression [60], the VirB binding site required for transcriptional anti-silencing of this promoter lies over 1 kb upstream of the primary icsP TSS [52,61]. To date, it remains unclear how silencing and anti-silencing of the icsP promoter occurs from such remote sites.…”
Section: H-ns and Its Role In The Regulatory Cascade Controlling Tmentioning
confidence: 99%
“…In contrast to icsA expression, which is primarily regulated by the transcriptional activator VirF (1,21,36), our previous studies have revealed that expression of icsP is regulated by VirB (4,18,46), a transcriptional activator whose expression is controlled directly by VirF. VirB, which directly controls the expression of many virulence-associated genes carried on the Shigella virulence plasmid (4,21,46), is maximally produced at 37°C, the temperature within the human host (30).…”
mentioning
confidence: 94%
“…2A) (14). Although it is possible that the LacZ protein is more stably maintained in the S. flexneri background than in E. coli, leading to higher ␤-galactosidase activity, this seems unlikely because LacZ activity has been shown to decline during stationary phase, when lacZ is expressed from another promoter in S. flexneri (39).…”
Section: Resultsmentioning
confidence: 99%